Injudicious and Excessive Procurement of Drugs in Tamil Nadu - CAG of India (CAG of India)
RAMO, Madurai and DMRHS (ESI) did not follow the prescribed medicine indenting procedure, based on the number of patients, resulting in locking up of Government funds of INR 16.39 crore in the form of excess procured medicines.